Impact of genetic and non-genetic factors on growth profile in Malpura and Avikalin lambs - Sharma, R C; Arora, A L; Kumar, R; Narula, H K (The Indian Journal of Animal Sciences, 2012)
Records on 1 405 lambs pertaining to Malpura and Avikalin sheep were utilized to assess the impact of certain genetic and non-genetic factors on growth profile traits, and their relative contributions to the total variability were quantified. Results revealed that breed influenced all the body weights significantly barring birth weight. Body weights from birth to yearling age were significantly influenced(P